2003
DOI: 10.1007/s00251-003-0559-8
|View full text |Cite
|
Sign up to set email alerts
|

A functional polymorphism in the promoter/enhancer region of the FOXP3/Scurfin gene associated with type 1 diabetes

Abstract: FOXP3/Scurfin, a member of forkhead/winged-helix proteins, is involved in the regulation of T-cell activation, and essential for normal immune homeostasis. The FOXP3/Scurfin gene is located on chromosome Xp11.23, which includes one of the type 1 diabetes susceptible loci. Therefore, we investigated whether the human FOXP3/Scurfin gene might be a new candidate gene for type 1 diabetes. We first screened the human FOXP3/Scurfin gene for microsatellite and single nucleotide polymorphisms. Next, we performed an as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
4
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 42 publications
1
115
4
3
Order By: Relevance
“…These results are in contrast with those of Bassuny et al (12), who studied a Japanese sample set of 199 patients and 289 control subjects and reported a weak disease association of the (GT)15 allele of the microsatellite marker located between exon Ϫ1 and exon 1 of FOXP3 (and named J17 in our study). In our sample set, this marker did not show any evidence of association with type 1 diabetes (Tables 1 and 2).…”
contrasting
confidence: 56%
“…These results are in contrast with those of Bassuny et al (12), who studied a Japanese sample set of 199 patients and 289 control subjects and reported a weak disease association of the (GT)15 allele of the microsatellite marker located between exon Ϫ1 and exon 1 of FOXP3 (and named J17 in our study). In our sample set, this marker did not show any evidence of association with type 1 diabetes (Tables 1 and 2).…”
contrasting
confidence: 56%
“…In this context, polymorphisms in the promoter region of genes coding for molecules strictly linked to the function of Treg may alter gene expression impacting on Treg activity [27]. Indeed, polymorphisms in the FOXP3 promoter gene sequence appear to confer a significant susceptibility to type 1 diabetes in the Japanese population [28] or to be associated with an increased risk of psoriasis in a Chinese population [29]. Our observation that the rs2294020 SNP in the promoter region of the FOXP3 gene is associated with AA is in line with the above considerations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that genetic defects in FOXP3 may lead to its altered levels and functionality and, indeed, autoimmune disorders have been related to various deleterious mutations in FOXP3 [34][35][36][37][38]. With respect to vitiligo, polymorphisms of FOXP3 have been associated with predispostion to the development of the disease (Table 2) [39-41].…”
Section: Forkhead Box P3mentioning
confidence: 99%